DOMINANTS OF POEMS IN PROSE BY MARKO CHEREMSHYNA - Tkachenko, Tetiana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article examines the formal and substantive features of the prose-poetic miniatures of Marko Cheremshyna (Ivan Semanyuk; 1874–1927). In particular, it singles out the themes and problems of the works; clarifies the role of names and the specifics of the presentation (rhythmization, story and narrator); analyzes prominent images-symbols and the meaning of visual, tactile and audio components; outlines the accents of semantic gradation (from personal to national and universal). The investigation studies figurative and expressive means (repetition, rhetorical construction, personification, parallelism, antithesis, etc.) and organization of the artistic text (framing, ellipses, subjectivism, lyricism, intimacy); highlights features of the writer’s idiostyle.